MARKETING APPROACH TO MANAGEMENT OF TOURIST PRODUCT FORMATION - BILYK, Victoriia; CHERNYAVSKA, Olga; VOYNIKOVA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Modern business conditions require market entities operating in the tourism industry to constantly monitor external and internal factors that have a direct impact on their activities. The authors of the article claim that the development of the market, and at the same time, the development of consumers, by increasing their requirements for a tourist product, requires enterprises to improve the efficiency of their activities by applying innovative, complex approaches to managing the process of forming a tourist product.The analysis of modern literary sources carried out by the authors of the article showed the insufficiency of substantiated methodical tools for the comprehensive implementation of marketing elements when managing the process of forming a tourist product of a marketing approach. Thus, the main task of the research is to provide business entities that manage the process of forming a tourist product in conditions of uncertainty with a scientifically based, improved analytical and comprehensive tool for confronting modern socio-political and economic challenges. Within the scope of the study, the authors clarified the definition of managing the process of formation of a tourist product in the marketing approach and it is proposed to understand it as the planning of comprehensive customer service, the organization of its promotion on the market of tourist products at a specified price, through optimal sales channels and the construction of effective communication with target market segments.The article establishes the sequence of the process of forming a tourist product, which, according to the authors, covers the definition of demand and supply in the tourist market; definition of functional features of the product; generation and selection of ideas; formation of a strategy and tactics for the development of a tourist product; development of a marketing strategy for product implementation on the tourist market; market testing; assessment of economic and social efficiency; corrective actions, product modification; introduction of the product to the tourist market. The authors identified the main factors that form the value for consumers of a tourist product, and also provided a comparative description of the key roles of management and marketing in the process of forming a tourist product. The authors focused special attention on the development of a marketing complex in the field of tourism, which differs from existing approaches in that it covers both internal and external elements.
Keywords: tourism product; tourism product formation; management; marketing approach; marketing complex